The Interaction Effects of Leader and Follower Conscientiousness on Person-Supervisor Fit Perceptions and Follower Outcomes: A Cross-Level Moderated Indirect Effects Model. Issue 3 (8th August 2019) - Guay, Russell P.; Kim, You-Jin; Oh, In-Sue; Vogel, Ryan M.
ABSTRACT: The primary purpose of this study is to examine how the cross-level interaction between leader and follower conscientiousness influences person-supervisor (PS) fit perceptions, which in turn impact follower work attitudes and organizational citizenship behavior (OCB). Based on a sample of 1, 204 participants in 167 work teams, the results of our cross-level moderated indirect effects model show that highly conscientiousness followers whose leaders also have high levels of conscientiousness experience enhanced perceptions of PS fit which result in higher levels of job satisfaction and OCB and lower levels of intention to quit. The study suggests that high leader conscientiousness serves as a supportive situational cue that motivates followers to more fully express their conscientiousness and act in ways consistent with their conscientiousness.